The effect of foreign ownership on stock return volatility with financial ratio as control variables - Erric Wijaya; Sofi Nurhazizah; Syamsyul Samsudin (Jurnal Fokus Manajemen Bisnis, 2025)
The capital market in Indonesia is an attractive investment destination for both domestic and foreign investors. It allows investors with excess funds to invest in various securities to obtain returns. However, volatility is a risk factor in investing, prompting investors to monitor volatility levels to make informed decisions. This study seeks to examine the impact of independent variables, particularly foreign ownership, in conjunction with control variables including company size, leverage, book to market ratio, and turnover on stock return volatility. The sample comprises 33 mining industry businesses listed on the Indonesia Stock Exchange from 2019 to 2023, harnessing secondary quantitative data. The study utilizes panel data regression analysis. The data was analyzed using Eviews software. The results demonstrate that foreign ownership and leverage exert a modest negative influence on stock return volatility, as does the book to market ratio. In contrast, business size and turnover positively enhance stock return volatility, with turnover exerting the most substantial influence. Investors will allocate their assets to a huge enterprise. The turnover variable exerts the most significant impact on stock return volatility. This is because investors typically examine patterns in a company's turnover rate while trading shares in the capital market.